Dairy Product Consumption and Prostate Cancer Risk in the US (P05-034-19). (13th June 2019) - Preble, Isabella; Zhang, Zhenzhen; Kopp, Ryan; Garzotto, Mark; Bobe, Gerd; Shannon, Jackilen; Takata, Yumie
Abstract: Objectives: We prospectively investigated the association between dairy product intake and prostate cancer risk among men in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) cohort. Methods: Pre-diagnostic dairy product intake was assessed using a validated food frequency questionnaire. Incident prostate cancer was ascertained by study visits, local cancer registries, or self-reports and only pathologically-verified cases were included in the analysis. In addition to overall prostate cancer, we classified cases by severity (early vs late stage, or low vs high Gleason scores). Using multivariate Cox regression models, we estimated hazard ratios (HR) and 95% confidence intervals (CI) for associations of prostate cancer risk with dairy product intake, as total (all dairy products), by fat content (low- or high-fat), or by fermentation methods (fermented or non-fermented). Results: Among 49, 472 men, 4134 were diagnosed with prostate cancer during an average follow-up period of 11.2 years. The median total dairy product intake was 101 g/1000 Kcal. Total dairy product consumption was not statistically significantly associated with risk of any prostate cancer or stratified by disease severity. The HR (95% CI) comparing the highest with the lowest quartiles of total dairy product intake was 1.05 (0.96–1.15) for overall prostate cancer risk and ranged from 1.00 (0.88–1.14), for risk of prostate cancer with high-Gleason score, to 1.24 (0.93–1.66), for risk of late-stage prostate cancer. The only statistically significant finding in our stratified analyses was a positive association between high-fat dairy product intake and late-stage prostate cancer risk (HR = 1.37, 95% CI = 1.04–1.82, P-trend  = 0.02). However, associations with high-fat dairy intake did not differ by stage ( P  = 0.15), suggesting a chance finding for the positive association with late-stage prostate cancer. Conclusions: These preliminary findings do not support the previously-reported harmful impact of dairy product consumption on prostate cancer risk among US men. The observed association of high-fat dairy intake with late-stage prostate cancer needs to be confirmed in other studies. Funding Sources: This study was funded by the Oregon Health & Science University/Oregon State University Cancer Prevention and Control Initiative.